Patterns of Multiple Victimization Among Maltreated Children in Navy Families. Issue 5 (30th September 2013) - Grasso, Damion J.; Saunders, Benjamin E.; Williams, Linda M.; Hanson, Rochelle; Smith, Daniel W.; Fitzgerald, Monica M.
<x xml:space="preserve">Abstract</x> The current study examined the cumulative risk associated with children's exposure to multiple types of parent‐inflicted victimization. The sample was comprised of 195 children who were 7 to 17 years old (64.1% female and 48.2% non‐White) at the time of referral to the United States Navy's Family Advocacy Program due to allegations of sexual abuse, physical abuse, or parental intimate partner violence. We conducted an exploratory latent class analysis to identify distinct subgroups of children based on lifetime victimization. We hypothesized that at least 2 classes or subgroups would be identified, with 1 characterized by greater victimization and poorer outcomes. Results indicated that 3 classes of children best fit the data: (a) high victimization across all 3 categories, (b) high rates of physical abuse and witnessing intimate partner violence, and (c) high rates of physical abuse only. Findings indicated that the high victimization class was at greatest risk for alcohol and substance use, delinquent behavior, and meeting criteria for posttraumatic stress disorder (PTSD) and/or depression 1 year later (odds ratio = 4.53). These findings highlight the serious mental health needs of a small but significantly high‐risk portion of multiply victimized children entering the child welfare system.